At spille på den store scene: – om performativitet og teatralitet i Christoph Schlingensiefs aktion Bitte liebt Österreich! - Gade, Solveig (Peripeti, 2021)
In »Acting on the big stage« Gade demonstrates the analytical gains in applying both a theory of performativity and a theory of theatricality to describe two different levels of staging and their interaction in Christoph Schlingensiefs performance Bitte liebt Österreich – Auslander Raus (2000).